A study of aftershocks of 20 October 1991 Uttarkashi earthquake (MAUSAM, 1995)
The Uttarkashi earthquake of 20 October 1991, which caused widespread damage in the Galhwal Himalayan region, was followed by a prominent aftershock. activity extending over a period of about two months. The aftershock activity was monitored using temporary networks established after the mainshock and the permanent stations in operation in the region. About 142 aftershocks could be located accurately using the data of these stations. The b-value of the Gutenberg-Richter's relationship for the aftershock sequence works out to be 0.6. The temporal distribution of the aftershocks suggests a hyperbolic decay with a decay constant (p) of 1.17. Macroseismic observations derived from field surveys show good agreement with the instrumentally determined source parameters.